PENGARUH EKSTRUSI DAN PROTEKSI DENGAN TANIN PADA TEPUNG KEDELAI TERHADAP PRODUKSI GAS TOTAL DAN METAN SECARA IN VITRO - Sajati, Ganang; Prasetyo, Bambang Waluyo Hadi Eko; Surono, Surono (Animal Agriculture Journal, 2012)
The purpose of this study was to examine the influence of combined treatmentsof the extrusion process and the addition of a natural source of tannins (tea and orgambier wastes) of the total gas and methane production in soybean flour.The materials used in this study were soybean meal, tea waste, gambier, cowrumen fluid, alcohol, CO2, McDougall solution, 15% H2SO4, 0,5 N NaOH, 0,5 N HCl,1% PP indicator and distilled water. The instruments used were analytical scales, testtubes, oven, extruder machine, waterbath, centrifuge, vacuum flaks, CO2 gas cylinder,100ml syringes glass equipped with silicone hoses and clips to be closed and opened,vaccuntainer, erlenmeyergas chromatography, special flute tube and distillation flask,glass beaker, Erlenmeyer, incubator, pipettes, measuring instruments, magnetic stirrer,peristaltic pump to drain the rumen fluid and heater. This study used completelyrandomized design in 2x3 factorials and 3 replicates by a-factor (a0 = no extruided anda1= extruded) and b-factor(b0= no tannins, b1= tea waste tannins, b2= gambier tannin).The parameters observed including total gas and methane production, the data weretaseted by usisng analysis of varience and followed by the Duncan test.The results indicate that there is no interaction between the extrusion and theaddition of tannins to total gas production, while the production of methane gas does notindicate any influence (p < 0.05). It is concluded that the extrusion and protection withnatural tannins of soybean flour have impacted on decreased in the production of totalgas and methane production.